2000
DOI: 10.1007/s004250000321
|View full text |Cite
|
Sign up to set email alerts
|

Control of gravimorphogenesis by auxin: accumulation pattern of CS-IAA1 mRNA in cucumber seedlings grown in space and on the ground

Abstract: Cucumber (Cucumis sativus L.) seedlings grown in microgravity developed a peg on each side of the transition zone between hypocotyl and root, whereas seedlings grown in a horizontal position on the ground developed a peg on the concave side of the gravitropically bending transition zone. The morphological features of the space-grown seedlings were similar to those of seedlings grown in a vertical position on the ground with their radicles pointing down: both became two-pegged seedlings. Morphogenesis of cucumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…The Cholodny-Went hypothesis proposes that a gradient of auxin is generated as a result of a gravity signal, stimulating a gradient of growth rate changes in cells across the tissue (Lomax, 1997). This hypothesis has been supported by studies on auxin redistribution (Lomax, 1997) and by the observation that gravistimulation results in asymmetrically induced auxin-responsive genes (McClure and Guilfoyle, 1989;Li et al, 1991;Kamada et al, 2000;Rashotte et al, 2001). In the oat pulvinus, 24 h of gravistimulation results in asymmetrical changes in free IAA levels with a 2.5-fold increase in free IAA in the lower one-half compared with the upper one-half of the oat pulvinus (Brock et al, 1991;Kaufman et al, 1995).…”
supporting
confidence: 55%
“…The Cholodny-Went hypothesis proposes that a gradient of auxin is generated as a result of a gravity signal, stimulating a gradient of growth rate changes in cells across the tissue (Lomax, 1997). This hypothesis has been supported by studies on auxin redistribution (Lomax, 1997) and by the observation that gravistimulation results in asymmetrically induced auxin-responsive genes (McClure and Guilfoyle, 1989;Li et al, 1991;Kamada et al, 2000;Rashotte et al, 2001). In the oat pulvinus, 24 h of gravistimulation results in asymmetrical changes in free IAA levels with a 2.5-fold increase in free IAA in the lower one-half compared with the upper one-half of the oat pulvinus (Brock et al, 1991;Kaufman et al, 1995).…”
supporting
confidence: 55%
“…It has been suggested that auxin is a factor that regulates peg formation (Witztum and Gersani, 1975;Takahashi and Scott, 1994;Kamada et al, 2000) as application of exogenous auxin induces peg formation on the convex side of the transition zone (Witztum and Gersani, 1975;Kamada et al, 2000). It has also been found that, in cucumber seedlings grown in a horizontal position, the levels of free indole-3-acetic acid (IAA) are more abundant in the concave side than in the convex side (Kamada et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…This gravity response of Mock 92.6 6 6.5 7.4 6 6.5 0.0 6 0.0 10 25 M TIBA 92.6 6 6.5 7.4 6 6.5 0.0 6 0.0 10 24 M TIBA 3.5 6 3.0* 96.5 6 3.0* 0.0 6 0.0 10 23 M TIBA 2.4 6 4.1* 88.4 6 4.8* 9.3 6 8.5* CsPIN1 localization occurred on the upper side of the transition zone and was consistent with the findings of spaceflight experiments . Gravistimulation is suspected to induce asymmetric auxin distribution in the transition zone and influence the location of peg formation Kamada et al, 2000Kamada et al, , 2003Saito et al, 2004Saito et al, , 2005. The application of TIBA, an inhibitor of auxin efflux, induces peg formation on the upper side of the transition zone of cucumber seedlings grown horizontally .…”
Section: Change In Cspin1 Accumulation In the Endodermis Of The Transmentioning
confidence: 99%
“…Both endogenous indole-3-acetic acid (IAA) concentration and auxin-inducible gene expression are significantly reduced on the peg-suppressed side (the upper side) of the transition zone Kamada et al, 2000). Application of exogenous auxin induces the development of a peg on the upper side of the transition zone in a horizontal position .…”
mentioning
confidence: 99%